Data Analysis of Informatics Engineering Students of Islamic University of Kuantan Singingi - Harianja Harianja; Nofri Wandi Al-Hafiz; Jasri Jasri (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2023)
Increasing student enrolment is the hope of any study program, including the study program at the Islamic University of Kuantan Singingi, especially the Informatics Engineering study program. During its existence, the Informatics Engineering program has experienced ups and downs in the number of students. This circumstance naturally affects the workload of the Informatics Engineering lecturers and the burden on the university's operating costs. So far, efforts have been made to increase the number of students, but this has not been done by analyzing existing student data. This study aims to analyze the existing student data in the hope that the results of this analysis can be useful for the Informatics Engineering study program at the Kuantan Singingi Islamic University of Kuantan Singingi to make decisions to increase the number of students in the future. Students in the Informatics Engineering study program come from different regions in Kuantan Singingi Regency and the surrounding districts. This is an opportunity for the university to analyze and visualize areas with a large number of enrollees. Using R programming, this student data can be easily visualized and presented.